Harmonizing Privacy Rights Protection in Electronic Transaction with Roscoe Pound’s Legal Principle - Suraji, Suraji; Prabowo, Ipop Abdi (Indonesian Journal of Advocacy and Legal Services, 2025)
The rapid development of information technology is significantly impacting the lives of humans. This technology enables transfer between regions, thereby threatening the right to privacy. However, the progress of the era related to electronic transactions will continue, necessitating the protection of privacy rights in electronic transactions, through harmonization with the legal principles of Roscoe Pound. A normative legal study was conducted with a statutory and conceptual method, then data were collected through literature studies and analyzed using descriptive-qualitative statistics. Privacy data protection has been implicitly regulated in Electronic Information and Transactions (ITE) and Personal Data Protection (PDP) Law, as well as Government Regulation concerning the Implementation of Electronic Systems and Transactions (PP PSTE). The concept of law as social engineering positions ITE and PDP as key instruments in the formation and development of society. Meanwhile, the balance is seen when a regulation has accommodated the interests, of both state, community, and individual, showing the legal thinking side of Roscoe Pound. Policymakers need to pay more attention to how policies are made in accordance with Roscoe Pound's legal principle to achieve the main objective.